Interest in complementary and alternative medicine among participants in a study on cancer prevention by green tea extract: results from an expert-based survey of MIRACLE trial participants - Melzer, Anna; Sturm, Niklas; Rohlmann, Friederike; Muche, Rainer; Stingl, Julia; Ettrich, Thomas J.; Seufferlein, Thomas (BMC complementary medicine and therapies, 2025)
Although chemopreventive strategies such as acetylsalicylic acid have shown potential in cancer prevention, they also entail adverse effects. This leads to growing interest in “natural” compounds, such as plant-based extracts, which may offer preventive benefits with fewer side effects. However, little is known aboutindividuals' personal attitudes towards conventional medications and complementary or alternative therapies when they are eligible for various cancer screening and prevention programmes. The present study aims to investigate the attitude toward medications and various therapies, as well as their prescription, among subjects participating in a clinical trial on the prevention of colorectal adenomas using green tea extract. A further goal was to assess whether the study predominantly attracted individuals with a strong preference for natural products or a more diverse set of opinions.